2021
DOI: 10.1029/2020ja029067
|View full text |Cite
|
Sign up to set email alerts
|

Climate Changes in the Upper Atmosphere: Contributions by the Changing Greenhouse Gas Concentrations and Earth's Magnetic Field From the 1960s to 2010s

Abstract: Greenhouse gases (GHGs) in the Earth's atmosphere, including CO 2 , CH 4 , H 2 O, and O 3 , absorb as well as emit infrared radiation. At lower altitudes where the air is dense, they are optically thick to outgoing infrared radiation and thus produce a heating effect. In contrast, at higher altitudes where the air is increasingly tenuous, they become optically thin to outgoing infrared radiation and therefore, produce a cooling effect. Note that the main role of O 3 in the atmosphere is as a solar ultraviolet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 55 publications
2
18
0
Order By: Relevance
“…Over Millstone Hill above the altitude of 220 km, cooling trends are stronger in ISR measurements than in the WACCM-X model. These discrepancies between the WACCM-X model and ISR data sets were also reported by Qian et al (2021).…”
Section: Summary and Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Over Millstone Hill above the altitude of 220 km, cooling trends are stronger in ISR measurements than in the WACCM-X model. These discrepancies between the WACCM-X model and ISR data sets were also reported by Qian et al (2021).…”
Section: Summary and Discussionsupporting
confidence: 60%
“…The increasing concentration of anthropogenic greenhouse gases (GHGs) leads to global warming in the lower atmosphere but can cool the upper atmosphere (Laštovička, 2015, 2021; Laštovička et al., 2006; Roble & Dickinson, 1989). However, the observed upper atmospheric cooling could also be caused by long‐term changes in geomagnetic activity (Liu et al., 2021; Mikhailov, 2006), secular changes in the Earth's magnetic field (Cnossen, 2014, 2020a; Qian et al., 2021; Yue et al., 2018), increased gravity wave activity (Oliver et al., 2013), and also other drivers which are in debate (Laštovička, 2015; Oliver et al., 2014, 2015, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These auroral changes in TEC are therefore also likely to be driven primarily by changes in the Earth’s magnetic field. However, in other parts of the world, the increase in CO 2 concentration probably plays a more important role, causing a negative trend in peak electron density and TEC (e.g., Qian et al., 2021).…”
Section: Spatial Patterns Of Trendsmentioning
confidence: 99%
“…The increase in atmospheric CO 2 concentration is thought to be the main driver of the global mean cooling and contraction of the upper atmosphere (e.g., Laštovička et al., 2006), with other trace gases playing a relatively minor role (Qian et al., 2013). The secular variation in the Earth's magnetic field also drives significant long‐term trends in the upper atmosphere, in particular in the ionosphere, although these vary strongly with location and largely cancel out in a global average (Cnossen, 2014, 2020; Qian et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…are of natural origin. However, lately using whole atmosphere model simulations Qian et al (2021) found that trends in the thermosphere were predominantly driven by greenhouse gases, whereas in the foF2, hmF2 and Te the role of greenhouse gases and of the secular change of the geomagnetic field were comparable in some regions. However, globally the role of magnetic field change is negligible because locally it is both positive and negative.…”
Section: Introductionmentioning
confidence: 99%